Rancang Bangun dan Analisis Kinerja Saluran udara pada Simulator Trainer Airbag - Solachuddin Al Ayyubi; Yuniarto Agus W (Universitas Muhammadiyah Metro, 2026)
Passive safety systems such as airbags are crucial for reducing the risk of fatal injuries in the event of a crash. The deployment speed of an airbag depends heavily on its mechanical design and electronic controls. This study aims to determine the effect of variations in valve channel diameter 2.5 mm, 5 mm, and 8 mm on the deployment response time of the driver-side airbag. The experimental method was conducted using an ATmega328 microcontroller-based airbag vehicle safety simulator trainer. In this test, a solenoid valve was used to regulate airflow with valve orifice diameters of 2.5 mm, 5 mm, and 8 mm. An ADXL345 sensor was used to provide the collision trigger signal to the microcontroller, while an HC-SR04 ultrasonic sensor was used to detect when the airbag began to deploy. Based on experimental analysis, it was concluded that the diameter of the valve channel significantly affects the inflation rate. The smaller the valve channel diameter, the faster the airbag response time. Conversely, the larger the channel diameter, the longer it takes for the airbag to inflate.